Biological Significance of microRNA Biomarkers in ALS—Innocent Bystanders or Disease Culprits? - Foggin, Sophie; Mesquita-Ribeiro, Raquel; Dajas-Bailador, Federico; Layfield, Rob (Frontiers in Neurology, 2019)
MicroRNAs (miRNAs) represent potential biomarkers for neurodegenerative disorders including amyotrophic lateral sclerosis (ALS). However, whether expression changes of individual miRNAs are simply an indication of cellular dysfunction and degeneration, or promote functional changes in target gene expression relevant to disease pathogenesis, is unclear. Here we used bioinformatics to test the hypothesis that ALS-associated miRNAs exert their effects through targeting genes implicated in disease aetiology. We documented deregulated miRNAs identified in studies of ALS patients, noting variations in participant cohorts, tissue samples, miRNA detection or quantification methods used, and if performed, the functional or bioinformatic assessments. Despite this lack of experimental standardisation, overlap of many deregulated miRNAs between studies was noted. However, direction of reported expression changes did not always concur. The use of in silico predictions of target genes for the most commonly deregulated miRNAs, cross-referenced to previously identified ALS genes, did not support our hypothesis. Specifically, although deregulated miRNAs were predicted to commonly target ALS genes, random miRNAs showed similar properties. To investigate further biological patterns potentially observed in the deregulated miRNAs, we grouped them by their tissue source, showing that for a core of frequently detected miRNAs, blood/plasma/serum could be useful for profiling experiments. We conclude in silico predictions of gene targets of deregulated ALS miRNAs, at least using currently available algorithms and ALS associated genes, are unlikely to be sufficient in informing disease pathomechanisms. We advocate experimental functional testing of candidate miRNAs and their predicted targets, and a concerted move towards standardisation of protocols for biomarker identification.